Pharmacokinetic and pharmacodynamic characterization of OROS® and immediate-release amitriptyline - Gupta, Suneel K (Blackwell Science Inc, 1999)
AIMS: To characterize the pharmacokinetics of amitriptyline and its metabolite nortriptyline following OROS® and IR treatments, and to correlate them with anticholinergic side-effects. METHODS: The pharmacokinetics and safety of amitriptyline following administration of an osmotic controlled release tablet (OROS® and an immediate release (IR) tablet were evaluated in 14 healthy subjects. In this randomized, open label, three-way crossover feasibility study, the subjects received a single 75 mg OROS® tablet, three 25 mg IR tablets administered every 8 h, or 3×25 mg IR tablets administered at nighttime. In each treatment arm serial blood samples were collected for a period of 84 h after dosing. The plasma samples were analysed by gas chromatography for amitriptyline and its metabolite nortriptyline. Anticholinergic effects such as saliva output, visual acuity, and subject-rated drowsiness and dry mouth were measured on a continuous scale during each treatment period. RESULTS: Following dosing with OROS® (amitriptyline hydrochloride), the mean maximal plasma amitriptyline concentration C(max) (15.3 ng ml(−1)) was lower and the mean t(max) (25.7 h) was longer than that associated with the equivalent IR dose administered at nighttime (26.8 ng ml(−1) and 6.3 h, respectively). The bioavailability of amitriptyline following OROS® dosing was 95% relative to IR every 8 h dosing, and 89% relative to IR nighttime dosing. The metabolite-to-drug ratios after the three treatment periods were similar, suggesting no change in metabolism between treatments. The relationships between plasma amitriptyline concentration and anticholinergic effects (e.g. reduced saliva weight, dry mouth, and drowsiness) were similar with all three treatments. Of the anticholinergic effects, only decreased saliva weight and dry mouth correlated well with plasma amitriptyline concentrations; drowsiness did not. There was no apparent correlation between anticholinergic effects and the plasma nortriptyline concentration. CONCLUSIONS: The bioavailability of OROS® (amitriptyline hydrochloride) was similar to that of the IR treatments and the pharmacokinetics of amitriptyline after OROS® dosing may decrease the incidence of anticholinergic effects compared with that seen with nighttime dosing of the IR formulation. Therefore, this controlled-release formulation of amitriptyline may be appropriate for single daily administration.